Branched‐chain fatty acids in the vernix caseosa and meconium of infants born at different gestational ages. Issue 7 (6th May 2021) - Li, Weidi; Jie, Liang; Yu, Renqiang; Jin, Qingzhe; Jiang, Shanyu; Yin, Qitao; Wei, Wei; Wang, Xingguo
Abstract: The functional lipid components found in breast milk, vernix caseosa, and meconium are Branched‐chain Fatty Acids (BCFA). The goal of this study was to establish the existence of BCFA in vernix and meconium in infants born at different gestational ages. TLC plates and GC‐MS were examined for the lipids in vernix caseosa and meconium. The results indicated that there were nine BCFA in vernix caseosa, including iso ‐12:0, anteiso ‐13:0, iso ‐14:0, iso ‐15:0, anteiso ‐15:0, iso ‐16:0, anteiso ‐17:0, iso ‐18:0, and iso ‐20:0. Five BCFA ( iso ‐12:0, anteiso ‐13:0, iso ‐14:0, iso ‐15:0, and anteiso ‐15:0) were not contained in the meconium, suggesting that some of the BCFA may be digested and consumed by infants. In the vernix caseosa, the content of BCFA in triacylglycerol (TAG) and free fatty acid (FFA) was 15.59% and 11.82%, respectively. The vernix caseosa's wax ester fraction contained the highest content of BCFA, reaching up to 16.81%. The carbon chain length of fatty acids (FA) ranged from 12 to 24 in the vernix caseosa and 14 to 22 in meconium samples. The gestational age was likely to affect BCFA concentrations, with the vernix caseosa and meconium BCFA content being significantly higher in full‐term infants than in preterm infants ( p  < .001). Further research is required into the relationship between BCFA and gut microbiotas. Abstract : The content of BCFA in the vernix and meconium was significantly higher in full‐term infants than in preterm infants. BCFA may be digested and absorbed in the infants' gastrointestinal tract.